ANALYSIS OF NATIONAL AND FOREIGN EXPERIMENTS ON WORKING WITH GIFTED STUDENTS IN TEACHING MOTHER TONGUE (Web of Teachers: Inderscience Research, 2024)
This article covers the use of national and foreign experience in bringing students ' talents to the surface when teaching native language subjects in the higher education system.